PELAKSANAAN PERNIKAHAN ADAT SUKU ANAK DALAM DALAM PERSPEKTIF UU NO 1 TAHUN 1974 - Hamzah, Iri (Al-Mazaahib: Jurnal Perbandingan Hukum, 2012)
Indonesian Marriage Law (UU No. 1/1974) has any problems in its implementing. This regulation conducted by government as a tool of unification of marriage law in order to anticipate legal uncertainty. There are three sistems of law in Indonesia; Adat/Customary law, Islamic law, and Western Law. UU No. 1/1974 is expected to be a solution of plurality of legal in Indonesia. However, this regulation had not able to protect that plurality, especially Adat law. Many of Indonesia's indigenous peoples remain insist running their customary marriage law and override the provisions in the legislation that has been legislated. This happens in the Suku Anak Dalam/Orang Rimba Jambi until now. Many of their marriage practices were inconsistent with the provisions of Law No. 1 of 1974. Most of them still adhere to animism- dynamism beliefs, had a way to measure maturity bride, and no concept of the guardian, witness, and also the recording of the marriage. This fact requires the government to review the provisions of Law No. 1 of 1974 in order to accommodate customary law currently applied until now.